Differences in circulating cardiac troponin I and T in acute and chronic cardiac disease. (3rd October 2022) - Zimmermann, T; Koechlin, L; Walter, J; Kimenai, D; Nestelberger, T; Boeddinghaus, J; Lopez-Ayala, P; Puelacher, C; Gualandro, D; Strebel, I; Diebold, M; Twerenbold, R; et al.
Abstract: Background: Clinical practice and guidelines assume that cardiac troponin I (cTnI) and cTnT are interchangeable, reflecting identical pathophysiological processes. However, it is unknown if cTnI and cTnT really are equivalent measures in different pathophysiological settings. Purpose: To highlight potential differences in the release of cTnI and cTnT. Methods: Large pooled cohort analysis including extensively characterized individuals, stratified into three groups: no cardiac disease (normal aging), chronic cardiac disease, and acute cardiac disease. Circulating cTnI and cTnT concentrations were measured blinded to clinical data using high-sensitivity assays (hs-cTnI-Architect, hs-cTnT-Elecsys) and their ratio calculated. Findings were validated using a second hs-cTnI assay (hs-cTnI-Clarity). Results: Among 8719 individuals, 29% female, 10% had no known cardiac disease, 71% chronic cardiac disease, and 20% acute cardiac disease. Baseline characteristics including renal function were comparable between individuals with chronic and acute cardiac disease. Normal aging (without cardiac disease) was associated with a disproportional increase in cTnT versus cTnI (low cTnI/cTnT ratio, median 0.50, IQR 0.38–0.68). Although older, patients with chronic cardiac disease had a slightly higher cTnI/cTnT ratio (median 0.53, IQR 0.37–0.79, p<0.05). In contrast, in patients with acute cardiac disease, cTnI concentrations were disproportionally elevated compared to cTnT concentrations, resulting in a cTnI/cTnT ratio of 1.96 (IQR 0.93–4.73, p<0.001). Internal validation using a second hs-cTnI assay confirmed these findings. Conclusion: These findings suggest relevant differences in the release of cTnI and cTnT with a greater release of cTnT versus cTnI in normal aging and a disproportional increase in cTnI versus cTnT in acute cardiac disease. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swiss National Science Foundation